Neurophysiological changes accompanying reduction in upper limb motor impairments in response to exercise-based virtual rehabilitation after stroke: systematic review. (December 2021) - Ellis, Fiona; Kennedy, Niamh C.; Hancock, Nicola J.; Pomeroy, Valerie M.
Abstract: Background: Virtual reality-augmented therapist-delivered exercise-based training has promise for enhancing upper limb motor recovery after stroke. However, the neurophysiological mechanisms are unclear. Objective: To find if neurophysiological changes are correlated with or accompany a reduction in motor impairment in response to virtual reality-aided exercise-based training. Data sources: Databases searched from inception to August 2020: MEDLINE, AMED, EMBASE, PUBMED, COCHRANE, CINHAL, PROQUEST and OPEN GREY. Eligibility criteria: Studies that investigated virtual reality-augmented exercise-based training for the upper limb in adults with stroke, and, measured motor impairment and neurophysiological outcomes. Studies that combined VR with another technology were excluded. Data extraction and synthesis: Using pre-prepared proformas, three reviewers independently: identified eligible studies, assessed potential risk-of-bias, and extracted data. A critical narrative synthesis was conducted. A meta-analysis was not possible because of heterogeneity in participants, interventions and outcome measures. Results: Of 1387 records identified, four studies were eligible and included in the review. Overall, included studies were assessed as having high potential risk-of-bias. The VR equipment, and control interventions varied between studies. Two studies measured motor impairment with the Fugl-Meyer Assessment but there was no commonality in the use of neurophysiological measures. One study found improvement in neurophysiological measures only. The other three studies found a reduction in motor impairment and changes in neurophysiological outcomes, but did not calculate correlation coefficients. Conclusion: There is insufficient evidence to identify the neurophysiological changes that are correlated with, or accompany, reduction in upper limb motor impairment in response to virtual reality-augmented exercise-based training after stroke. Systematic Review Registration Number PROSPERO 2017 CRD42017071312